Birth in times of war - An investigation of health, mortality and social class using historical clinical records - Nadine Geiger; Sebastian Wichert (Center for Economic Studies and ifo Institute (CESifo), 2019)
While World War II (WWII) is often employed as natural experiment to identify long-term effects of adverse early-life and prenatal conditions, little is known about the short-term effects. We estimate the short-term impact of the onset of WWII on newborn health using a unique data set of historical birth records ranging from December 1937 to September 1941. Furthermore we investigate the heterogeneity of this effect with respect to health at birth and for different social groups. To evaluate potential channels for our results, we explore how birth procedures changed. While we do not find any effects on birth weight and asphyxia, perinatal mortality increases immediately after the onset of WWII. The mortality effect is driven by live births and strongest for very low birth weight infants. A decline in quality of medical care due to the sudden conscription of trained physicians to military service is the most likely mechanism for our findings.
Keywords: I10; I18; N34; N44; 330; infant mortality; early-life health; health care supply